Children learning to use technologies through play: A Digital Play Framework. (1st August 2014) - Bird, Jo; Edwards, Susan
Abstract Digital technologies are increasingly acknowledged as an important aspect of early childhood education. A significant problem for early childhood education has been how to understand the pedagogical use of technologies in a sector that values play‐based learning. This paper presents a new framework to understand how children learn to use technologies through play. The Digital Play Framework is based on the sociocultural concept of tool mediation and Corrine Hutt's work regarding epistemic and ludic activity as basis for understanding play. The Digital Play Framework presents a series of indicators for how children learn to use technologies as cultural tools, first by exploring the functionality of technologies through epistemic activity, and second by generating new content through ludic activity.